Does the New European Driving Cycle (NEDC) really fail to capture the NOX emissions of diesel cars in Europe?. (March 2017) - Degraeuwe, Bart; Weiss, Martin
Abstract: Tests with Portable Emissions Measurement Systems (PEMS) have demonstrated that diesel cars emit several times more NOX on the road than during certification on the New European Driving Cycle (NEDC). Policy makers and scientists have attributed the discrepancy to the unrealistically low dynamics and the narrow temperature range of NEDC testing. Although widely accepted, this assumption was never been put under scientific scrutiny. Here, we demonstrate that the narrow NEDC test conditions explain only a small part of the elevated on-road NOX emissions of diesel cars. For seven Euro 4–6 diesel cars, we filter from on-road driving those events that match the NEDC conditions in instantaneous speed, acceleration, CO2 emissions, and ambient temperature. The resulting on-road NOX emissions exceed by 206% (median) those measured on the NEDC, whereas the NOX emissions of all unfiltered on-road measurements exceed the NEDC emissions by 266% (median). Moreover, when applying the same filtering of on-road data to two other driving cycles (WLTP and CADC), the resulting on-road NOX emissions exceed by only 13% (median) those measured over the respective cycles. This result demonstrates that our filtering method is accurate and robust. If neither the low dynamics nor the limited temperature range of NEDC testing can explain the elevated NOX emissions of diesel cars, emissions control strategies used during NEDC testing must be inactive or modulated on the road, even if vehicles are driven under certification-like conditions. This points to defeat strategies that warrant further investigations by type-approval authorities and, in turn, limitations in the enforcement of the European vehicle emissions legislation by EU Member States. We suggest applying our method as a simple yet effective tool to screen and select vehicles for in-depth analysis by the competent certification authorities. Graphical abstract: Abstract : We demonstrate that diesel cars emit several times more NOX on the road than on the NEDC certification cycle even when driven under the similar dynamic and temperature conditions.